Evaluation of dietary natural mineral materials as an antibiotic replacer on growth performance, non‐specific immune responses and disease resistance in rainbow trout, Oncorhynchus mykiss. (24th March 2017) - Won, Seonghun; Moniruzzaman, Mohammad; Lee, Seunghan; Hong, Jeongwhui; Park, Jung‐Keug; Kim, Sangeun; Bai, Sungchul C
Abstract: We evaluated the effects of some dietary natural mineral materials as an antibiotic replacer based on growth performance, non‐specific immune responses and disease resistance in juvenile and subadult rainbow trout, Oncorhynchus mykiss . First experiment, juvenile rainbow trout averaging 2.7 ± 0.02 g (mean ± SD) were fed one of the six experimental diets; a basal commercial diet as a control (CON), CON with oxytetracycline (OTC), with yellow loess (YL), with Macsumsuk ® (MS), with Song‐Gang ® stone (SG) and with barley stone (BS) at 0.4% of each diet. At the end of 8‐week feeding trial, weight gain (WG), specific growth rate (SGR), feed efficiency (FE) and protein efficiency ratio (PER) of fish fed YL diet were significantly higher than those of fish fed CON diet. Non‐specific immune responses such as superoxide dismutase (SOD), myeloperoxidase (MPO), lysozyme (LYS) activity and oxidative radical production of fish fed YL diet were higher than those of fish fed CON diet. At the end of 15 days of challenge test with Aeromonas salmonicida, average cumulative survival rate of fish fed YL diet was significantly higher than that of fish fed BS and CON diets. However, there were no significant differences among fish fed YL, SG and OTC diets. Second experiment, subadult rainbow trout averaging 261.5 ± 3.5 g (mean ± SD) were fed one of the four experimental diets for 22 weeks: CON, and CON with OTC, YL or SG at 0.4% of each diet. At the end of feeding, growth performance of fish fed SG and YL diets was significantly higher than that of fish fed CON diet. Non‐specific immune responses in terms of SOD, MPO, LYS and NBT of fish fed SG and YL diets were significantly higher than those of fish fed CON diet. However, there were no significant differences among the fish fed YL, SG and OTC diets. The results indicate that dietary yellow loess or Song‐gang ® stone at 0.4% of diet could replace oxytetracycline in juvenile and subadult rainbow trout.